(3CQHY eSGFd eeG JSJZdX HGdSDGd YfgG HYV GdUfYGJjIGdNGdbjf dCgd GdHjJs - (3fhQ GdOjf CHh YHO Gddg MejOGf Hf jMji GdbGSeis; (3MejOGf Hf jMji Hf MejOGf Hf GdbGSe Hf GdMSf Hf EHQGgje Hf SdjeGf GdbGSej, CHh YHO Gddgs
(3ChdgG (B:s
(3GdChdi (B: (3SDGdge Yf GdfXQ ai EKHGJ GdUGfY JYGdi gd jMUd Hg GdYde Efg JYGdi bGOQ hYGde s
(3BNQgG (B:s
(3hcPdc GdSDGd Yf GdaQb Hjf GdebJVi hGdebJVi hGdYdI hGdMce hbS Ydi Pdc Je GdeLehY HMeO Gddg hefg s
(3Vef eLehY s
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdSjO eMeO Hf eMeO Hf ESeGYjd GdeXgQ s
Keywords: (3GdJGQjNs